Needs analysis of a RELIEVE-based STEM-PjBL e-module for applied science education - Elza Heryensi; Fitri April Yanti; Rendy Wikrama Wardana; Mochamad Lutfi Firdaus (Education and Development Research, 2025)
This research aims to analyze the needs and specifications of the Renewable Energy Literacy through the Exploration of Various Natural Materials (RELIEVE) e-module, which is integrated with STEM-PjBL to support applied science learning in universities. This qualitative research involved five lecturers who were selected purposively, with data collected through semi-structured interviews, then transcribed, verified, and analyzed using a thematic approach. The results of the study show three main findings. First, students need learning that is applicable, contextual, interactive, and problem-solving based to develop critical and creative thinking skills. Second, the STEM-PjBL approach is considered appropriate because it is able to integrate science, technology, engineering, and mathematics concepts through contextual projects that increase student learning engagement. Third, the required e-modules must be digital, easily accessible through devices, structured, project-based, and provide authentic assessments to measure high-level thinking skills (HOTS), especially critical and creative thinking skills. These findings confirm that the development of the RELIEVE e-module has the potential to be a strategic pedagogical innovation to strengthen renewable energy literacy and support the sustainable energy transition while contributing to curriculum development and further research on the effectiveness of STEM-PjBL-based learning in higher education.